(untitled) (REMUNOM, 2025)
The number of elderly people has increased considerably in both wealthy countries and developing nations. The rise in life expectancy and the growing proportion of elderly individuals in the population require special attention in the prevention of bone diseases and the maintenance of quality of life. Therefore, understanding the benefits and risks of supplementation is essential to guide clinical practices and health policies. This research aims to elucidate the importance and risks of vitamin D supplementation in the elderly. The general objective is to discuss the significance of vitamin D and the potential risks of its supplementation in older adults. The research methodology employed was a literature review. Searches were conducted between January and March 2025 in the following databases: PubMed, SciELO, LILACS, and Google Scholar. The analyzed studies indicate that vitamin D is essential for bone metabolism and fall prevention, significantly contributing to the reduction of fracture risks in the elderly. However, supplementation should only be administered in diagnosed cases of deficiency, adhering to recommended limits to avoid complications.